Characterization and source apportionment of single particles from metalworking activities. (1st February 2021) - Arndt, Jovanna; Healy, Robert M.; Setyan, Ari; Flament, Pascal; Deboudt, Karine; Riffault, Véronique; Alleman, Laurent Y.; Mbengue, Saliou; Wenger, John C.
Abstract: Industrial metalworking facilities emit a variety of air toxics including volatile organic compounds, polycyclic aromatic hydrocarbons (PAHs) and heavy metals. In order to investigate these emissions, a 1-month multi-instrument field campaign was undertaken at an industrial site in Grande-Synthe, Dunkirk (France), in May and June 2012. One of the main objectives of the study was to provide new information on the chemical composition of particulate matter with aerodynamic diameters smaller than 2.5 μm (PM2.5 ) in the vicinity of metalworking facilities. An aerosol time-of-flight mass spectrometer (ATOFMS) was deployed to provide size-resolved chemical mixing state measurements of ambient single particles at high temporal resolution. This mixing state information was then used to apportion PM2.5 to local metalworking facilities influencing the receptor site. Periods when the site was influenced by metalworking sources were characterised by a pronounced increase in particles containing toxic metals (manganese, iron, lead) and polycyclic aromatic hydrocarbons (PAHs) with a variety of chemical mixing states. The association of specific particle classes with a nearby ferromanganese alloy manufacturing plant was confirmed through comparison with previous analysis of raw materials (ores) and chimney filter particle samples collected at the facility. Particles associated with emissions from a nearby steelworks were also identified. The contribution of local metalworking activities to PM2.5 at the receptor site for the period when the ATOFMS was deployed ranged from 1 to 65% with an average contribution of 17%, while the remaining mass was attributed to other local and regional sources. These findings demonstrate the impact of metalworking facilities on air quality downwind and provide useful single particle signatures for future source apportionment studies in communities impacted by metalworking emissions. Graphical abstract: Image 1 Highlights: Particles assigned to a ferromanganese facility and a steelworks based on composition. Metalworking particle composition and mixing state is complex and diverse. Metalworking emissions contributed 17% to PM2.5 on average at the receptor site. Metalworking is the dominant source of metals and polycyclic aromatic hydrocarbons.